Pelatihan Ketrampilan Mendengarkan Empatik Aktif Untuk Meningkatkan Kedekatan Guru dan Anak - Ika Setya Mahanani; Sri Redatin Retno Pudjiati; Patricia Patricia (JIP (Jurnal Intervensi Psikologi), 2018)
Closeness in teachers-child relationship in early childhood education has a positive impact in increasing the involvement of children with school, improve academic achievement, prosocial behavior and reduce child problem behavior. This study aims to improve closeness in teacher-child relationship in early childhood education through active empathic listening skills training. Participants are four early childhood education teachers. Teacher-child relationships are measured based on teachers' perceptions of their relationship with children. Teachers fill the questionnaire by her perception of her relationship with 5 children. This research uses quasiexperimental method with one group pretest-posttest design. The results of statistical data processing showed a very significant change in the increase of closeness level of teacher-child relationship between pretest and post test 1 (z = -3.560, p = 0.000 < 0,01), and post test 1 with posttest 2 (z = -3.220, p = 0.001 < 0,05). Active empathic listening skill showed significant improvement between pre test and post test 1 (z = -1.826, p = 0.34 < 0,05) and no significant improvement between post test 1 and post test 2 (z = -1.342, p = 0.090 > 0,05).Keywords: active empathic listening skill, closeness, teacher-child relationships, early childhood education teachers, early childhood